Nativity Differences in Youths’ Weight Trajectories: Foreign-Born Health Integration during the Transition to Adulthood - Jackson, Margot I. (2011)
Nativity differences in youths’ health in the United States are striking, with the children of foreign-born parents showing more favorable outcomes than those of native-born parents. Very little is known about how inequalities evolve within the same individuals over time, or more generally about life cycle aspects of the health integration of youth with migration backgrounds. Using data from the National Longitudinal Study of Adolescent Health, I examine nativity differences in trajectories of weight gain during adolescence and early adulthood, as well as the degree to which trajectories are stratified by race/ethnicity and socioeconomic status. Do nativity differences converge, diverge or remain stable over time, and how are patterns socially stratified within and across nativity groups? I find that first-generation adolescents begin at a lower weight than their third generation peers and gain weight at a significantly slower pace, producing meaningful differences by early adulthood. More complex examination of the relationship between nativity and weight gain reveals additional differences by ethnicity: the foreign-born advantage over time does not extend as strongly to Hispanic adolescents. The findings demonstrate how the health-related integration of foreign-born youth is tied to race/ethnicity and socioeconomic circumstances, and suggest the need to examine the ways in which social circumstances and health change together.